0.3(3y-12)=6-2(y-1)

Simple and best practice solution for 0.3(3y-12)=6-2(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.3(3y-12)=6-2(y-1) equation:


Simplifying
0.3(3y + -12) = 6 + -2(y + -1)

Reorder the terms:
0.3(-12 + 3y) = 6 + -2(y + -1)
(-12 * 0.3 + 3y * 0.3) = 6 + -2(y + -1)
(-3.6 + 0.9y) = 6 + -2(y + -1)

Reorder the terms:
-3.6 + 0.9y = 6 + -2(-1 + y)
-3.6 + 0.9y = 6 + (-1 * -2 + y * -2)
-3.6 + 0.9y = 6 + (2 + -2y)

Combine like terms: 6 + 2 = 8
-3.6 + 0.9y = 8 + -2y

Solving
-3.6 + 0.9y = 8 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-3.6 + 0.9y + 2y = 8 + -2y + 2y

Combine like terms: 0.9y + 2y = 2.9y
-3.6 + 2.9y = 8 + -2y + 2y

Combine like terms: -2y + 2y = 0
-3.6 + 2.9y = 8 + 0
-3.6 + 2.9y = 8

Add '3.6' to each side of the equation.
-3.6 + 3.6 + 2.9y = 8 + 3.6

Combine like terms: -3.6 + 3.6 = 0.0
0.0 + 2.9y = 8 + 3.6
2.9y = 8 + 3.6

Combine like terms: 8 + 3.6 = 11.6
2.9y = 11.6

Divide each side by '2.9'.
y = 4

Simplifying
y = 4

See similar equations:

| (5u-2)(1+u)=0 | | (2x^2-6x+16x+8x-24x+16)*(x^2+5x-2)=(2x+4)*(x^2+5x-2)*(x+4) | | 7(x+8)+5=7x+4 | | (8-5)(2-7)= | | x+2x+16=97 | | 40x^2+97x+45= | | 4-4x=5x+4 | | -354-228= | | 2x-84=22 | | 10x^2+45x=25 | | 2+14x=30 | | 0.5+45+x+2x=150 | | 11(t-4)+7t=6(3t+4)-12 | | 7=7b+4b | | 2w-6x-y+4w+18x-4y= | | 7(56+85)7x(57x+70)=30x | | -4(6y-9)-y=-4(y-4) | | 354+228= | | 5+(4x-12)=140 | | 5x(4x-12)=140 | | 12+11d=-18-4d | | -345+228= | | 5x-3y+8w+2y-2w+7x= | | x+2y=-63 | | 27x-x^2=180 | | x+(x+275000)=625000000 | | 135-6x=39x+15 | | 16r=64 | | 12x-43=5x+19 | | 2x+3x-7=38 | | 2r^2+r+6=0 | | 14x-(25-5x)=10+15 |

Equations solver categories